ASPECTS OF FURTHER DEVELOPMENT OF HYDROENERGY ACCORDING TO THE MATERIALS OF THE SCIENTIFIC AND PRACTICAL CONFERENCE «RENEWABLE ENERGY AND ENERGY EFFICIENCY IN THE XXI CENTURY» 2023 - Vasko, P. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2023)
The main results of reports at the hydropower section, in which specialists from Ukraine and the Republic of Uzbekistan took part, were considered and summarized. A total of 12 reports were presented, 3 of which related to issues of large hydropower, and 9 reports related to small hydropower. The main trend of the content of the reports was to cover the issues of creation and operation of hydroelectric power plants with minimal impact on the environment.